2020
DOI: 10.1155/2020/8833863
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Control Rockburst Mechanism of Coal and Rock Mass with Bursting Liability in Deep Mining

Abstract: In order to study the mechanism of the dynamic disaster of rockburst in a deep coal mine and the prevention and control measures of weakening shock, the MTS815.03 servocontrolled rock mechanics test system is used to test the coal, rock, and combined specimens with the buried depth of nearly 1200 m in Xinwen Mining Area. And their mechanical properties, energy evolution, and bursting properties are studied and analyzed. The rationality of the test results is also verified by the in-situ engineering practice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…According to laboratory tests on coal specimens, it has been shown that elastic energy drops slowly as confining pressure increases. As a result, improving the surface restraint and support strength of roadways is an essential step in insitu engineering practice to limit the occurrence of roof failure [23].…”
Section: Rock Pressure Theoriesmentioning
confidence: 99%
“…According to laboratory tests on coal specimens, it has been shown that elastic energy drops slowly as confining pressure increases. As a result, improving the surface restraint and support strength of roadways is an essential step in insitu engineering practice to limit the occurrence of roof failure [23].…”
Section: Rock Pressure Theoriesmentioning
confidence: 99%
“…However, less research has been carried out in the area of rock burst stress wave attenuation. Dou et al [18][19][20] described a strain-softening numerical model based on the Hoek-Brown failure criterion that was developed to evaluate the destressing efficiency of RDHB in selected underground coal mines. Ju et al [21,22] proposed the concept of "high strength, strong pressure relief, and integrity" roadway support and the impact of "staggered peak pressure regulation + blasting top cut strong support" according to the violent and large-deformation characteristics of a rock burst in roadways.…”
Section: Introductionmentioning
confidence: 99%
“…ere are diversified rockburst mechanisms, and the main factors are generally related to underground geometrical shape and geological conditions [7][8][9]. Rockburst in itself is the sudden release of elastic strain energy stored in the rock mass under the excavation unloading effect, and it is an energy-driven dynamic instability phenomenon.…”
Section: Introductionmentioning
confidence: 99%